العلاقة بين ثخانة المخاطية الفموية والامتصاص العظمي حول عنق الغرسات السنية - خليل, عبد الكريم; أسعد, منذر; بلة, نور الهدى (Latakia University Journal -Medical Sciences Series, 2013)
تهدف الدراسة إلى تقييم تأثير ثخانة النسيج المخاطي فوق قمة السنخ على الامتصاص العظمي حول عنق الغرسة السنية، وذلك خلال سنة من المتابعة . بلغ عدد الغرسات (24) غرسة، أنجزت على 9 مرضى من الجنسين ممن لديهم درد خلفي سفلي. تم تقسيم العينة إلى مجموعتين , المجموعة الأولى " المخاطية أكثر من 2مم " 12 غرسة، و المجموعة الثانية " المخاطية حتى2مم" 12 غرسة , و في كلتا المجموعتين تم وضع (6) غرسات (الشاهدة) عند مستوى قمة العظم السنخي، و ( 6)غرسات (الاختبار) فوق مستوى قمة العظم السنخي بـ 2 مم . أظهرت النتائج وجود زيادة في معدل الخسارة العظمية حول عنق الغرسة في المجموعة الثانية، وبفروق ذات دلالة إحصائية. نستنتج أن ثخانة المخاطية عند الغرس تؤثر على مقدار الخسارة العظمية حول عنق الغرسة حيث يحدث امتصاص زائد إذا كانت المخاطية رقيقة (حتى 2 مم) وقت الغرس. The aim of the study was to evaluate the influence of the mucosal tissue thickness on the crestal bone resorption around dental implants during a year of follow-up. Nine patients of both sexes included in this study received 24 implants. Patients in the sample were divided into two groups: group I (mucosa above 2 mm, and 12 implants), and group II (mucosa up to 2 mm, and 12 implants). Implants in each group were divided into two groups: a control where 6 implants were placed at the crest level, and a test where (6) implants were placed 2mm supracrestally. The results revealed that there was an increase in crestal bone loss in group 2 with statistically significant differences. To conclude, the initial thickness of mucosa at the time of implant placement affects crestal bone loss; increased bon loss occurs when the tissue thickness is 2 mm or less at the time of implant placement.